A frog in the throat?. Issue 10 (28th September 2017) - Waseem, Hunniya; Welch, Matthew
Abstract : Clinical introduction: A 44-year-old woman, with an unremarkable medical history, presented in the middle of the night with discomfort in her throat. She described being assaulted by an assailant who put his 'fist in her mouth', trying to suffocate her. On examination, she had normal observations and no signs of injury, other than scratch marks around her mouth; she reported no odynophagia and was able to swallow fluids readily. During examination, she complained that lying flat made her increasingly uncomfortable and was causing burgeoning dyspnoea. She had lateral soft tissue radiography of her neck as shown in figure 1 . Question: What is the diagnosis? Caustic stricture of the oesophagus Pharyngeal perforation Pharyngeal pouch Boerhaave's syndrome